Bioinformatic Analysis of a Set of 14 Temperate Bacteriophages Isolated from Staphylococcus aureus Strains Highlights Their Massive Genetic Diversity - Suárez, Cristian Alejandro (2022)
Epidemiology and virulence studies of Staphylococcus aureus showed that temperate bacteriophages are one of the most powerful drivers for its evolution not only because of their abundance but also because of the richness of their genetic payload. Here, we report the isolation, genome sequencing, and bioinformatic analysis of 14 bacteriophages induced from lysogenic S. aureus strains from human or veterinary (cattle) origin. The bacteriophages belonged to the Siphoviridae family; were of similar genome size (40 to 45 kbp); and fell into clusters B2, B3, B5, and B7 according to a recent clustering proposal. One of the phages, namely, vB_SauS_308, was the most unusual one, belonging to the sparsely populated subcluster B7 but showing differences in protein family contents compared with the rest of the members. This phage contains a type I endolysin (one catalytic domain and noncanonical cell wall domain [CBD]) and a host recognition module lacking receptor binding protein, cell wall hydrolase, and tail fiber proteins. This phage also lacked virulence genes, which is opposite to what has been reported for subcluster B6 and B7 members. None of six phages, taken as representatives of each of the four subclusters, showed activity on coagulase-negative staphylococci (excepted for two Staphylococcus hominis strains in which propagation and a very slow adsorption rate were observed) nor transducing ability. Immunity tests on S. aureus RN4220 lysogens with each of these phages showed no cross immunity.